2023
DOI: 10.1101/2023.01.25.525506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The memory of pathogenic IgE is contained within CD23+IgG1+memory B cells poised to switch to IgE in food allergy

Abstract: Food allergy is caused by allergen-specific IgE antibodies but little is known about the B cell memory of persistent IgE responses. Here we describe in human pediatric peanut allergy CD23+IgG1+ memory B cells arising in type 2 responses that contain peanut specific clones and generate IgE cells on activation. These type2-marked IgG1+ memory B cells differentially express IL-4/IL-13 regulated genes FCER2/CD23, IL4R, and germline IGHE and carry highly mutated B cell receptors (BCRs). Further, high affinity memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…The fact that we based our hypoallergen design off of our analysis of three bins of conformational IgG epitopes provokes the question as to whether these epitopes are the same as IgE epitopes. As discussed above, many studies have suggested that this is likely 13,17 . Indeed, the hexamutant mutations that reduced binding to the IgG cloned antibodies analysed in this study clearly also reduce IgE reactivity in the competitive ELISA and the PCA (Figures 5 and 6).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The fact that we based our hypoallergen design off of our analysis of three bins of conformational IgG epitopes provokes the question as to whether these epitopes are the same as IgE epitopes. As discussed above, many studies have suggested that this is likely 13,17 . Indeed, the hexamutant mutations that reduced binding to the IgG cloned antibodies analysed in this study clearly also reduce IgE reactivity in the competitive ELISA and the PCA (Figures 5 and 6).…”
Section: Discussionsupporting
confidence: 63%
“…These studies primarily identified IgG sequences but other studies have identified shared Ara h 2‐specific IgE and IgG antibody clones, 12,15,16 which supported a paradigm of sequential switching from IgG to IgE. A confirmation of this class switch was implied by Ota et al who again cloned similar public IgG immunoglobulin sequences and noted the memory of pathogenic IgE in IgG1 producing B‐cells 17 . Finally, sequential epitope mapping of serum IgE and IgG4 induced during peanut OIT have shown significant overlap 18 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This notion is supported by the correlation of CD23 + IL4R + IgG + MBCs transcribing IGHE and the production of pathogenic IgE 5 . Moreover, chronic exposure may allow extensive somatic hypermutations in the germinal center as indicated by high mutation levels of MBC2 6 …”
Section: Figurementioning
confidence: 93%
“…Moreover, chronic exposure may allow extensive somatic hypermutations in the germinal center as indicated by high mutation levels of MBC2. 6 Interestingly, IgG + CD21 high MBCs showed inhibitory receptor expression such as CD22 (Siglec-2). These inhibitory receptors may feature potential targets for depleting such long-lived MBC(2) s. However, exclusive targeting of allergen-specific MBCs may only be a mosaic in treating type 1 hypersensitivities.…”
mentioning
confidence: 99%